2003
DOI: 10.1111/j.1432-2277.2003.tb00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of specific stress response increases resistance of rat liver allografts to cold ischemia and reperfusion injury

Abstract: Heme oxygenase-1 (HO-1) has been shown to increase cellular resistance against oxidative injury, but the functional significance of this is currently obscure. We investigated the protective role of HO-1, induced by tin-protoporphyrin IX (SnPP), in attenuating liver transplantation injury. Lewis rats were intraperitoneally treated with saline as control, 50 pmol/kg of SnPP, or 2 mg/kg of cycloheximide (CHX) before SnPP injection. Gene expression of HO-1 was induced after either treatment with SnPP-or CHX + SnPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Despite overwhelming evidence that HO-1 can exert cytoprotective effects, there is a seemingly contradictory literature indicating that within 18-24 hr of SnPP administration, adaptive tissue responses arise which usher in profound tissue protection against superimposed injuries (e.g., ref. Atef, El-Fayoumi, Abdel-Mottaleb, & Mahmoud, 2017;Cukiernik, Mukherjee, Downey, & Chakabarti, 2003;Johnson, Delrow, & Zager, 2017;Johnson & Zager, 2018;Juncos et al, 2006;Kaizu et al, 2003;Panizzon, Dwyer, Nishimura, & Wallis, 1996;Sutherland et al, 2011;Uchida et al, 2003;Zager, 2015;Zager, Johnson, & Frostad, 2016). For example, our laboratory has reported that within 18 hr of SnPP injection, mice develop marked protection against diverse forms of ischemic and toxin-induced AKI (Johnson et al, 2017;Johnson & Zager, 2018;Zager, 2015;Zager et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite overwhelming evidence that HO-1 can exert cytoprotective effects, there is a seemingly contradictory literature indicating that within 18-24 hr of SnPP administration, adaptive tissue responses arise which usher in profound tissue protection against superimposed injuries (e.g., ref. Atef, El-Fayoumi, Abdel-Mottaleb, & Mahmoud, 2017;Cukiernik, Mukherjee, Downey, & Chakabarti, 2003;Johnson, Delrow, & Zager, 2017;Johnson & Zager, 2018;Juncos et al, 2006;Kaizu et al, 2003;Panizzon, Dwyer, Nishimura, & Wallis, 1996;Sutherland et al, 2011;Uchida et al, 2003;Zager, 2015;Zager, Johnson, & Frostad, 2016). For example, our laboratory has reported that within 18 hr of SnPP injection, mice develop marked protection against diverse forms of ischemic and toxin-induced AKI (Johnson et al, 2017;Johnson & Zager, 2018;Zager, 2015;Zager et al, 2016).…”
Section: Introductionmentioning
confidence: 99%